Identificación de factores de riesgo asociados a Cryptosporidium spp. en bovinos de Ubaté, Cundinamarca - Sánchez Camacho, José Julián (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: Infection by Cryptosporidium spp. It represents a health problem for both cattle and humans, and is associated with water contamination and poor management practices. This study aimed to identify risk factors linked to infection by Cryptosporidium spp. in the cattle population of Ubaté. A sample of 377 cattle was taken and fecal samples were collected directly from the animals' rectum. These samples were processed using the Ziehl-Neelsen staining technique to detect parasite cysts. The results revealed an overall prevalence of 13.26%, with males being more susceptible than females (28.57% vs. 12.67%). In terms of age groups, cattle aged 2-4 years had the highest prevalence, with 21.88%. Although no significant associations were found between infection and variables such as sex, age or breed, risk factors related to management practices were identified, such as the presence of livestock from other owners, renting pastures and purchasing animals. In addition, the water source, especially access to streams, is also significantly affected by the infection. In conclusion, this study highlights the need to address management practices and water access to prevent and control Cryptosporidium spp infection. in the Ubaté livestock farm, which will contribute to the health and productivity of livestock in this region of Cundinamarca, Colombia.